HUBUNGAN ANTARA MAJELIS TAKLIM DENGAN KELUARGA SAKINAH DI KAMPUNG REMPAK KECAMATAN SABAK AUH KABUPATEN SIAK - Kuramin, Siti; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aimed to determine the correlation between majelis taklim and sakinah family in Rempak village, Sabak Auh Sub-Regency, Siak Regency. This research was quantitative research that analyzed based on inferential statistic. The theory of the research was Functional theory which uses simple random sampling as the technique. from 147 population, 60 samples was taken by using Slovin formula. The samples as respondents was formed by using lottery technique. The results obtained in the field that the correlation between majelis taklim and sakinah family, based on qualification level of correlation, is on moderate level with 0,592 as the value of Pearson Correlation. Overall the participation of respondents in the majelis taklim, 50% of respondents included in very good category, 45% of the respondents in good category, and 5% of respondents in less good category. Meanwhile, the quality of sakinah family of respondents is 26,67% and categorized as very good, 70% of the respondents are in good category and 3.33% of respondents are in the less good category. Based on the significance value of Coefficient table obtained significance value that is equal to, 000 <0.05, so it can be concluded that the variable